A molecular Popeye: Li+@C60 and its complexes with [n]cycloparaphenylenes. Issue 12 (10th March 2023) - Freiberger, Markus; Solymosi, Iris; Freiberger, Eva Marie; Hirsch, Andreas; Pérez-Ojeda, M. Eugenia; Drewello, Thomas
Abstract : We compare the stability of [ n ]cycloparaphenylene ([ n ]CPP)-based host–guest complexes with Li + @C60 and C60 in the gas and solution phase. Our experiments reveal a significant increase in stability for the complexes featuring [9–12]CPP with Li + @C60 . Abstract : In this work, we compare for the first time the stability of [ n ]cycloparaphenylene ([ n ]CPP)-based host–guest complexes with Li + @C60 and C60 in the gas and the solution phase. Our gas-phase experiments reveal a significant increase in stability for the complexes featuring [9–12]CPP with Li + @C60 . This increased interaction strength is also observed in solution. Isothermal titration calorimetry shows for the formation of [10]CPP⊃Li + @C60 a two orders of magnitude larger association constant than that for the C60 analog. Additionally, an increased binding entropy is observed. This study contributes to a better understanding of host–guest complexes between [ n ]CPPs and endohedral metallofullerenes at a molecular level, which is the prerequisite for future applications.